Food and nutrition security under changing climate and socioeconomic conditions - Rosegrant, Mark W.; Sulser, Timothy B.; Dunston, Shahnila; Mishra, Abhijeet; Cenacchi, Nicola; Gebretsadik, Yohannes; Robertson, Richard D.; Thomas, Timothy S.; Wiebe, Keith D. (Elsevier, 2024)
Food and nutrition security have become increasingly critical concerns for policy makers given that the slow progress on eliminating these challenges has reversed in recent years, with an increase in the number of hungry people by 122 million (20 percent) between 2019 and 2022. In addition to rebuilding in the aftermath of the COVID-19 pandemic, the global food system faces inter-related challenges from climate change, trade disruptions, increasing scarcity of water and land, environmental degradation, and evolving food demand patterns, among other factors. This paper assesses prospects to 2050 for food and nutrition security with a focus on low- and middle-income countries around the world in the context of these broader food system changes. Measures of food security presented here include per capita food and kilocalorie availability, the number and prevalence of hungry people, and micronutrient availability. Projected outcomes are assessed using the latest version of the International Model for Policy Analysis of Agricultural Commodities and Trade (IMPACT) framework, a modeling system that combines information from climate models, crop simulation models, and river basin level hydrological and water supply and demand models linked to a global, partial equilibrium, multimarket agriculture sector model.